Penerapan TTG Smart Aquaphonik Untuk Membangkitkan Semangat Generasi Muda Karangduren - Pakisaji - Aripriharta, Aripriharta; Arfienda Miawa Tyassilva; Sunaryono; Mokh. Sholihul Hadi; Satia Nur Maharani; Annisa Firly Aprilia Putri; Muhiban Syabani (Departemen Teknologi Pertanian Universitas Hasanuddin, 2023)
Agricultural technology is one of the focus areas to be targeted in the next few years. The real way to achieve this goal is the transfer of aquaphonic technology. Karangduren is an area in Pakisaji District, Malang Regency which has limited land and is used as non-productive land. As non-productive land, it is then converted into aquaphonic agricultural land. Efforts to raise the spirit of the younger generation towards limited agricultural land, carried out community service in the form of implementing TTG on smart aquaphonic farming systems by utilizing IoT technology for regulating and monitoring nutrients, pH, and oxygen content. The method used is the direct implementation method with the community. Community service activities can increase public enthusiasm and awareness regarding the use of sub-optimal land into agricultural land in the form of aquaponics. The application of appropriate technology in the form of solar panels can be used as a source of power to turn on the water pump so as to save energy and costs.